2020
DOI: 10.1111/tpj.14789
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of legume nodulation by Pi deficiency is dependent on the autoregulation of nodulation (AON) pathway

Abstract: SUMMARY Inhibition of nodule development is one of the main adverse effects of phosphate (Pi) deficiency in legumes. Despite all of the efforts made over the last decades to understand how root nodules cope with Pi deficiency, the molecular mechanisms leading to the reduction in nodule number under Pi deficiency remain elusive. In the present study, we provide experimental evidence indicating that Pi deficiency activates the autoregulation of nodulation (AON) pathway, leading to a reduction in nodule numbers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 69 publications
(124 reference statements)
0
35
0
Order By: Relevance
“…The low Pi conditions induce RIC1, RIC2, and TML expression, suggesting the involvement of these genes in the low-nodulation phenotype of P. vulgaris under Pi-deficient conditions. RIC1 and RIC2 induction in response to Pi deficiency is likely dependent on PHOSPHATE STARVATION RESPONSE 1 (PHR1), a master transcription factor for Pi deficiency adaptation (Rubio et al, 2001;López-Arredondo et al, 2014;Isidra-Arellano et al, 2020). The putative cis-regulatory element P1BS, a PHR1-binding sequence (Bustos et al, 2010), was identified in RIC1 and RIC2 promoters, and this putative cis-element is conserved in promoter regions of RIC1 and RIC2 orthologs of other legumes, implying the involvement of PHR1 in this negative regulation of nodulation.…”
Section: Adaptations To Phosphate Deficiency Through Aonmentioning
confidence: 99%
See 1 more Smart Citation
“…The low Pi conditions induce RIC1, RIC2, and TML expression, suggesting the involvement of these genes in the low-nodulation phenotype of P. vulgaris under Pi-deficient conditions. RIC1 and RIC2 induction in response to Pi deficiency is likely dependent on PHOSPHATE STARVATION RESPONSE 1 (PHR1), a master transcription factor for Pi deficiency adaptation (Rubio et al, 2001;López-Arredondo et al, 2014;Isidra-Arellano et al, 2020). The putative cis-regulatory element P1BS, a PHR1-binding sequence (Bustos et al, 2010), was identified in RIC1 and RIC2 promoters, and this putative cis-element is conserved in promoter regions of RIC1 and RIC2 orthologs of other legumes, implying the involvement of PHR1 in this negative regulation of nodulation.…”
Section: Adaptations To Phosphate Deficiency Through Aonmentioning
confidence: 99%
“…Indeed, RIC1 and RIC2 expression induction by Pi deficiency is not observed in PHR1-silenced P. vulgaris hairy roots. Moreover, grafting experiments using P. vulgaris and soybean nark mutants demonstrated that this nodulation restriction under Pi deficiency is also a shoot-controlled negative regulatory system that depends on NARK (Isidra-Arellano et al, 2020). Since elevated TML mRNA levels in roots have been observed in response to low Pi levels, it is not surprising that miR2111 is also involved in this regulation.…”
Section: Adaptations To Phosphate Deficiency Through Aonmentioning
confidence: 99%
“…These defects may be associated with an auxin-cytokinin imbalance, upregulation of ethylene, abscisic acid (ABA), and jasmonate-related signaling pathways under Pi deficiency in common bean ( Isidra-Arellano et al, 2018 ). Recent studies have shown that the AON-related genes PvNIN , PvRIC1 , PvRIC2 , and PvTML are induced under conditions of Pi deficiency and their transcriptional activation is likely to be dependent on PHR1 ( Isidra-Arellano et al, 2020 ; Figure 2 ). These studies suggest that Pi deficiency inhibits the root nodule symbiosis in common bean and soybean through constitutive activation of the AON pathway under Pi deficiency ( Isidra-Arellano et al, 2020 ).…”
Section: The Role Of Phosphate Signaling and Transport In Symbiotic Nitrogen Fixationmentioning
confidence: 99%
“…Recent studies have shown that the AON-related genes PvNIN , PvRIC1 , PvRIC2 , and PvTML are induced under conditions of Pi deficiency and their transcriptional activation is likely to be dependent on PHR1 ( Isidra-Arellano et al, 2020 ; Figure 2 ). These studies suggest that Pi deficiency inhibits the root nodule symbiosis in common bean and soybean through constitutive activation of the AON pathway under Pi deficiency ( Isidra-Arellano et al, 2020 ).…”
Section: The Role Of Phosphate Signaling and Transport In Symbiotic Nitrogen Fixationmentioning
confidence: 99%
“…Low P availability severely suppresses nodule formation and development, two of the major processes that largely determine BNF capacity. It has been reported that phosphate (Pi) starvation negatively impacts critical early steps of rhizobial symbiosis through (1) limiting infection thread (IT) formation, (2) reducing the expression of genes participating in early nodulation processes, and (3) disrupting autoregulation of nodule numbers in Pi‐deficient seedlings (Isidra‐Arellano et al, 2018, 2020; Nasr‐Esfahani et al, 2017). After IT formation, another crucial step for effective N 2 fixation in legumes is nodule organogenesis, when rhizobia differentiate into intracellular N 2 ‐fixing bacteroids that subsequently expand into nodules (Oke & Long, 1999).…”
Section: Introductionmentioning
confidence: 99%